The Bedfordshire Schoolchild. elementary education before 1902 (Publications Bedfordshire Hist Rec Soc Ser., 1988)
The Bedfordshire Schoolchild: Elementary education before 1902 Amongst the documents from which extracts are taken are: the record of schools in the Bishop of Lincoln's Visitations 1717 and 1720; the returns to the Select Committee on Education of the Poor 1818; the 1833 education returns; grants to National and British schools 1835-1843; a report in 1844 of the HM School Inspector; the Church of England's enquiry into schools in 1846/7; the education census of 1851; Union workhouse schools; reports on child employment 1843-1867/8; extracts from school logbooks; the report on elementary education made under the Education Act 1870; and extracts from the minutes of school boards 1870-1903.